RESOLUSI KONFLIK KEAGAMAAN BERBASIS KEARIFAN LOKAL: STUDI ATAS PELA GANDONG DI AMBON - Ismail, Roni; Wakano, Abidin; Leasiwal, Genoveva (UIN Sunan Kalijaga Yogyakarta, 2022)
AbstractThis article aims to analyze the role of pela gandong as local wisdom used as a cultural conflict resolution in the 1999-2002 Ambon conflict. Using sociology of conflict approach, the theory of cultural conflict resolution, and methods of collecting observational data and interviews with Ambonese Muslims and Christians, this paper finds that, first, ethnocentrism is the main cultural cause of the Ambon conflict, and, second, the Ambon conflict is resolved and peace is built firmly through the cultural conflict resolution of pela gandong. With noble values, especially brotherhood, equality, equality, togetherness and tolerance, pela gandong is very effective in resolving cultural conflicts both during the Ambon conflict, post-conflict and in fostering peace until now. During the Ambon conflict, there was no conflict between Muslim and Christian countries that were bound by pela gandong. After the conflict occurred, pela gandong became the foundation of cultural conflict resolution in rebuilding peace, strengthening the capacity of Ambonese people